Airbus se in a duopoly with a weakened competitor, airbus can only be beaten by itself - Lindner, Katharina (2021)
This Work Project presents a valuation of Airbus SE, an aerospace and defence company. At the beginning of the report an overview of the company’s business segments is given. Followed by a presentation and discussion of the aerospace and defence sector including an analysis of the market demand, supply and trend as well as the industry’s and company’s growth potential. Finally, the valuation itself will be presented. On the basis of a DCF valuation Airbus SE’s share price for the target date 31.12.2020 is calculated. A forecast that results in a Buy recommendation for Airbus SE shares.